Effect Of Rubber Damper Stiffness And Tire Pressure To Reduce Ground Reaction Load Factor On Main Landing Gear Using Multi-Body Simulation (MBS) Rigid Model - Dony Hidayat (Jurnal Teknologi Dirgantara, 2019)
Landing Gear Drop Test (LGDT) utilizes the apparatus requiring a substantial time and cost. Virtual LGDT (vLGDT) using MSC ADAMS software is one of the solutions for initial stage to testing landing gear. From simulation with vsink 1.7 m/s and load 22000 N obtained contact/impact force that ensue in  MSC ADAMS was 73650 N, while from experimental was 73612 N. The difference between vLGDT and LGDT result is 0.05 %. To obtain ground reaction load factor below 3 in vsink = 3.05 m/s, the rubber damper should have stiffness in the range of 1900 - 2100 N/mm and for the tire pressure of  60 - 65 psi.